The Performance of State Civil Apparatus in Gorontalo Province: The Relationship with Emotional Intelligence, Spiritual Intelligence, Leadership, and Organizational Citizenship Behavior - Muhdar HM (Faculty of Economics and Business, University of Muhammadiyah Malang, 2018)
This study aims to find out and analyze the direct and indercet effect: emotional intelligence with state civil apparatus performnce of through leadership and OCB, spiritual intelligence with state civil apparatus performance of through leadership and OCB. Population is the whole state civil apparatus in Gorontalo Province which amounts 3155. Samples should be taken as many as 350 people and the worthy of only analized 250 questionnaires. The sampling technique using are multistage sampling (purposive sampling and random sampling). The data were analyzed by using of structural equations models (SEM) and program analysis of moment structure (AMOS) version 23. The results showed that emotional intelligence and spiritual intelligence of significant effect on the leadership; emotional intelligence and leadership of significant effect on OCB; emotional intelligence and OCB of significant effect on employee performance; spiritual intelligence does not significant effect on OCB and employee performance; the leadership does not significant effect on employee performance; emotional intelligence and spiritual intelligence effect on OCB through leadership variable; emotional intelligence and spiritual intelligence effect on state civil apparatus performance of through leadership variable; and emotional intelligence and spiritual intelligence effect on state civil apparatus performanc of through OCB variable.